1973
DOI: 10.1111/j.1432-1033.1973.tb03141.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Histidine Residues in Yeast Hexokinase

Abstract: Specific acylation of the histidine residues of yeast hexokinase with diethylpyrocarbonate at pH 6.1 or 7.5 leads to a partial and reversible inactivation of the enzyme.The carboethoxylation of the histidine residues at pH 7.5 was faster than at 6.1 and the loss in activity was also higher.However the difference in the amount of inactivation was related to a greater instability of the carboethoxylated enzyme at pH 7.5.When the carboethoxylation was carried out at pH 7.5 and at 0 "C, only the histidines residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1974
1974
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…However, using near-and far-UV CD, we did not observe any significant conformational changes between pH 8.5 and 4.0. Although pH 6.5 falls in the region of the pK a of the histidyl residues, Grouselle et al (30) showed that histidyl residues have no role in binding to the substrate or in catalysis. Viola and Cleland (31) have used the pH variation of the enzyme kinetic parameters, V max and V/K, to elucidate the chemical mechanism of the enzyme action.…”
Section: Ph-dependent Stability Andmentioning
confidence: 99%
“…However, using near-and far-UV CD, we did not observe any significant conformational changes between pH 8.5 and 4.0. Although pH 6.5 falls in the region of the pK a of the histidyl residues, Grouselle et al (30) showed that histidyl residues have no role in binding to the substrate or in catalysis. Viola and Cleland (31) have used the pH variation of the enzyme kinetic parameters, V max and V/K, to elucidate the chemical mechanism of the enzyme action.…”
Section: Ph-dependent Stability Andmentioning
confidence: 99%
“…The histidine residue of CaM was carbethoxylated with diethyl pyrocarbonate according to the method of Grousselle et al [17], as reported in detail by Walsh and Stevens [18]. CaM (1 mg/ml) was incubated at 23 "C in 0.1 M phosphate buffer.…”
Section: Ollier Chemical Modifications O F Cammentioning
confidence: 99%
“…Carboxyl groups have been reported to be involved in the action of yeast hexokinase (Pho et al, 1974), and from X-ray crystallographic data Anderson et al (1978) have observed what seems to be an interaction between an aspartyl residue and the 4-and 6-hydroxyl groups of the sugar substrate. There is evidence for the involvement of histidyl residues in the active site of the wheat germ enzyme (Higgins & Easterby, 1974), but this residue has been found not to be involved in either the binding of substrate or the catalysis of yeast hexokinase (Grouselle et al, 1973). ' The -log VI profiles both showed a "hump" attributed to a loss of activity in the pH region 7.5-5.5.…”
mentioning
confidence: 99%